Aesthetic Value of Wahyu Manggoloâs Kethoprak Performance Presenting Mahesa Jenar Series Alap-Alap Jentik Manis - -, Pujiati (Harmonia: Journal of Arts Research and Education, 2015)
The purposes of this research are (1) to find out the aesthetic value of Wahyu Manggoloâs kethoprak performances presenting Mahesa Jenar series Alap-alap Jentik Manis in the village of Tanjungsari, Jakenan in Pati Regency and (2) to depict the kethoprak performance there. This study uses a qualitative method depicting the aesthetic elements and the forming elements of the value in Wahyu Manggoloâs kethoprak. The techniques of data collection are an interview, an observation, and a documentation. The results showed that there are five elements as parts of an aesthetic value in the performance. Those elements are shape, story, character, content, and characteristic, while seven elements to form the value are unity, complexity, intensity, stimulation or determinant, consequents as a means of recording emotional levels, moods, and characters.